Investigating Strategies for Mitigating and Avoiding Expert Blind Spot Development in Teaching English Attributive Adjectives - Farisani Thomas Nephawe (English Department of Faculty of Tarbiyah and Teacher Training, 2023)
Teaching is a prominent paraphernalia that brings numerous insights for developing learners’ competence in educational concerns. However, teaching English to non-native learners poses challenges as innovative strategies are scant. Sometimes teachers overlook the difficulties experienced by novices when they approach a new English grammatical domain. Psychological expert blind spot sporadically and intuitively develops due to teachers’ ignorance. The paper investigated strategies for mitigating and avoiding expert blind spot in teaching English attributive adjectival phrases at Khwevha High School in Limpopo Province, South Africa. Quantitative and qualitative research approaches were adopted to corroborate the findings. A questionnaire was used to collect data from 35 selected Grade 10 respondents using a simple random sampling technique. Qualitatively, semi-structured interviews were conducted on two purposely sampled schoolteachers from Dzindi Circuit, based on the researcher’s preference for obtaining an in-depth understating of the topic. Initially, learners were incompetent in using adjectives but after employing ‘points of entry’, offering ‘explanations’, presenting ‘structures’ and checking ‘comprehension’ strategies, learners improved considerably. The paper underscores using the identified strategies to mitigate and avoid the advancement of the expert blind spot in teaching English attributive adjectives.